2024
DOI: 10.3390/coasts4020015
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Eukaryotes in Natural and Artificial Salt Marsh Pools

Marina Potapova,
Daiana Markarian,
Abigail King
et al.

Abstract: Microscopic eukaryotes are important components of coastal wetland ecosystems. The goal of this study was to investigate the diversity of microeukaryotes in the tidal pools of a New Jersey salt marsh and to compare the assemblages of natural and artificial pools excavated for controlling mosquito populations. We evaluated microeukaryotic assemblages using the amplicon sequencing of 18S and rbcL DNA markers and the microscopic identification of diatoms in water and sediment samples. 18S unique amplicon sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 128 publications
0
1
0
Order By: Relevance
“…lls the existing research gap by focusing on the temporal and spatial changes of microalgae and harmful algae in the SMPs. A recent molecular study revealed signi cant differences in microeukaryotes between natural and arti cial ponds in Tuckerton peninsula, New Jersey (Potapova et al 2024). However, their study was limited to a sampling event and did not cover spatial and temporal dynamics of HAB species in the ponds.…”
Section: Discussionmentioning
confidence: 99%
“…lls the existing research gap by focusing on the temporal and spatial changes of microalgae and harmful algae in the SMPs. A recent molecular study revealed signi cant differences in microeukaryotes between natural and arti cial ponds in Tuckerton peninsula, New Jersey (Potapova et al 2024). However, their study was limited to a sampling event and did not cover spatial and temporal dynamics of HAB species in the ponds.…”
Section: Discussionmentioning
confidence: 99%